O que é uma criança para a psicanálise? considerações sobre a estrutura e o infantil - Formigoni, Maria Claudia (2013)
The present work aims to research what a child for psychoanalysis is. So forth it is installed a differentiation between childhood, subject and childish. From a historic perspective, it is shown that the childhood, as it is conceived today, is a Modernity institution that gave a particular place to children and made feasible the uprising of so many speeches about child and childhood. It is outstand in the present work that Freud broke with the candor s ideal imputed to the children at that time, once he has revealed the infantile sexuality. Freud s works related to this matter, as the present essay shows, allow establishing an important distinction between childhood, as a life stage, and childish, conceived as an intrinsic sign in human psychism. In this way, it is concluded that child is not a psychoanalyst concept neither a notion with which psychoanalysis operates. Being said that, the present work sets forth the subject s concept approach as postulated by Lacan until 1958, which allows affirming that, for psychoanalysis, it is not about a child or an adult, but about unconscious subject. Starting from that, it is retaken the lacanian Oedipus Complex, from which becomes evident that, from the psychoanalysis perspective, there is in the structure a place that the child, as it is denominated by culture, occupies (the phallus) and, in fantasy, the mark of what is left from this place (the childish). What matter to psychoanalysis, therefore, and it is presented in a psychoanalysis process, is specific the childish postulated by Freud, i.e., what remains form the phallus place that every subject has once occupied